ΔFosB overexpression in the nucleus accumbens enhances sexual reward in female Syrian hamsters - Hedges, V.L. (2009)
Repeated activation of the mesolimbic dopamine system results in persistent behavioral alterations accompanied by a pattern of neural plasticity in the nucleus accumbens (NAc). As the accumulation of the transcription factor ΔFosB may be an important component of this plasticity, the question addressed in our research is whether ΔFosB is regulated by sexual experience in females. We have shown that female Syrian hamsters given sexual experience exhibit several behavioral alterations including increased sexual efficiency with naïve male hamsters, sexual reward, and enhanced responsiveness to psychomotor stimulants (e.g., amphetamine). We recently demonstrated that sexual experience increased the levels of ΔFosB in the NAc of female Syrian hamsters. The focus of this study was to explore the functional consequences of this induction by determining if the constitutive overexpression of ΔFosB by adeno-associated viral (AAV) vectors in the NAc could mimic the behavioral effects of sexual experience. Animals with AAV-mediated overexpression of ΔFosB in the NAc showed evidence of sexual reward in a conditioned place preference paradigm under conditions in which control animals receiving an injection of AAV-green fluorescent protein (GFP) into the NAc did not. Sexual behavior tests further showed that males paired with the AAV-ΔFosB females had increased copulatory efficiency as measured by the proportion of mounts that included intromission compared to males mated with the AAV-GFP females. These results support a role for ΔFosB in mediating natural motivated behaviors, in this case female sexual behavior, and provide new insight into the possible endogenous actions of ΔFosB.